An investigation of the socio-economic relationship between civil society and social capital on subjective well-being - Samuel Brown (2019)
An increase in the government’s interest in well-being over recent years has led to much new research in these fields. This thesis considers subjective well-being, exploring how it is affected by employment contracts, life events and religiosity. Since the economic crisis of 2008/9 there has been an increase in certain employment contracts (such as zero-hour contracts). The effect of these different employment contracts has been explored here, with a focus on whether omitting unemployed individuals from such research will bias the results. Big life events, such as unemployment, marriage, divorce, disability, etc. can have a big impact upon an individual’s well-being. These impacts have been investigated here, considering also anticipation (changes in well-being in the lead up to the event) and adaptation (changes to well-being following the event). There is also a focus on how individuals at different points along the well-being distribution respond differently to these life events. Religiosity has generally been found to have a positive impact upon well-being. However, this relationship has not considered the indirect impact that religiosity may have on well-being through its effects on social capital, income, employment status, marital status, education and health. These indirect effects are explored here, splitting the analysis by gender and religion/denomination. The research performed here identifies many vulnerable groups who suffer strong negative effects from employment, life events or religiosity. Therefore, this research has many policy implications.